Environmental risk factors for type 1 diabetes in Rome and province. Issue 8 (22nd July 2003) - Visalli, N; Sebastiani, L; Adorisio, E; Conte, A; De Cicco, A L; D'Elia, R; Manfrini, S; Pozzilli, P; ,
Abstract : Background: In subjects genetically susceptible to type 1 diabetes, exposure to environmental factors during the gestational period, the neonatal period, and the first years of life is thought to play an important role in triggering the immune process leading to β cell destruction. Aims: To investigate risk factors for inhabitants of continental Italy. Methods: A case-control study of 150 type 1 diabetes cases and 750 control subjects (age range 6–18 years) was carried out in Rome and its province, measuring the exposure to environmental risk factors. Results: Three environmental factors were found to occur significantly more in the diabetic group than in the controls. During the mothers' pregnancies, the one risk factor which proved to be higher in diabetics than in controls was maternal infectious disease. During the neonatal period, no risk factors associated with the disease were detected. During early life, eczema and a short duration of breast feeding (less than three months), occurred significantly more in diabetic cases than controls. Conclusion: Eczema and breast feeding for less than three months are risk factors for type 1 diabetes in a southern European population. The type, duration, and mode of treatment for infectious diseases during pregnancy need additional investigation as risk factors for type 1 diabetes.